A review of the species of Belostoma Latreille, 1807 (Hemiptera: Heteroptera: Belostomatidae) from the four southeastern Brazilian states - Ribeiro, Josi Ricardo Inacio (Zootaxa, 2007)
The species of the Neotropical genus Belostoma Latreille,1807 from southeastern Brazil are poorly known. Therefore here I review and key for the first time the Belostoma species from these southeastern states: Espírito Santo, Minas Gerais, Rio de Janeiro, and São Paulo. The following 22 species are recorded and redescribed: Belostoma anurum (Herrich-Schäffer), B. aurivillianum (Montandon), B. bergi (Montandon), B. bosqi De Carlo, B. candidulum Montandon, B. costalimai De Carlo, B. cummingsi De Carlo, B. dallasi De Carlo, B. dentatum (Mayr), B. dilatatum (Dufour), B. discretum Montandon, B. elongatum Montandon, B. foveolatum (Mayr), B. horvathi Montandon, B. micantulum (Stål), B. noualhieri Montandon, B. orbiculatum Estévez & Polhemus, B. plebejum (Stål), B. ribeiroi De Carlo, B. sanctulum Montandon, B. stollii (Amyot & Serville), and B. testaceopallidum Latreille. Three new records from this region are reported: B. bergi, B. bosqi, and B. elongatum. Belostoma minor (Palisot de Beauvois) and B. oxyurum (Dufour) probably do not occur in southeastern Brazil. The single record of the first species and the several records of the second one in the region are cases of misidentification. Nine new synonymies are established (junior synonymies within parentheses): B. candidulum (B. amici), B. costalimai (B. truxali), B. cummingsi (B. cachoeirinhensis), B. dilatatum (B. ripicolum), B. ribeiroi (B. lundbladi), B. stollii (B. brasiliensis; B. planum; and B. stolii), and B. testaceopallidum (B. grandicollum). Lectotypes are designated for B. aurivillianum, B. bergi, and B. discretum. Four characters have proven useful for species delimitation: the ratio between the greatest pronotal width and its length in the midline, the aspect of the prosternal keel, the pilosity pattern of the connexivum, and the ratio between the width of the ventral diverticulum and its length in ventral view. Lists with the morphological terms and characters suggested for these species are included, together with synonyms proposed by other taxonomists and morphologists.